2013
DOI: 10.3171/2013.3.spine121026
|View full text |Cite
|
Sign up to set email alerts
|

Spinal aneurysms: clinicoradiological features and management paradigms

Abstract: Object Spinal aneurysms (SAs) are rare lesions. The clinicoradiological features and the exact degree of their association with comorbid conditions such as arteriovenous malformations (AVMs) and coarctation of the aorta have not been definitively described. The ideal management paradigm has not been established. The authors reviewed literature to determine the clinical patterns of presentation, management, and outcome of spinal aneurysms. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 85 publications
(69 reference statements)
3
23
1
Order By: Relevance
“…The incidence of aneurysms could not be compared with other studies because only case reports or series including 1–4 cases have been published. A systematic review on spinal aneurysms showed that 55 (44.7%) were associated with an AVM and 68 (55.3%) were isolated spinal aneurysms not associated with an AVM; thus, isolated aneurysms are more commonly associated with SAVM 4. However, we did not observe any isolated spinal aneurysms in our study or any aneurysm associated with an epidural arteriovenous fistula, which is known to cause congestive venous myelopathy 14–17…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The incidence of aneurysms could not be compared with other studies because only case reports or series including 1–4 cases have been published. A systematic review on spinal aneurysms showed that 55 (44.7%) were associated with an AVM and 68 (55.3%) were isolated spinal aneurysms not associated with an AVM; thus, isolated aneurysms are more commonly associated with SAVM 4. However, we did not observe any isolated spinal aneurysms in our study or any aneurysm associated with an epidural arteriovenous fistula, which is known to cause congestive venous myelopathy 14–17…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, our study showed that hemorrhage of a spinal aneurysm was less common than reported in the literature. Aneurysms in our study were relatively common (4/8) in cervical cord areas, as found in a systemic review 4. Although we did not use surgical decompression to relieve the mass effect, there are several reports on surgical decompression or clipping of the feeding artery ligation 21 22…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In our series, these patient populations comprised nearly 40% of cases. Transplant has also been tied to isolated spinal arterial aneurysms as approximately 6% of patients in one systematic review were post-renal transplant 1. In our series, one patient presented post-cardiac transplant.…”
Section: Discussionmentioning
confidence: 95%